2021
DOI: 10.1007/s43440-021-00280-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the CCL2-CCR2 axis in depressive disorders

Abstract: Since affective disorders are considered to be underlain by the immune system malfunction, an important role in their pathophysiology is assigned to the proinflammatory mediators. Recently, chemokines, the group of chemotactic cytokines, have become a focus for basic and clinical scientists in the context of the development and treatment of brain diseases. Among them, chemokine CCL2 and its main receptor CCR2 have become candidate mediators of abnormal brain-immune system dialogue in depression. Besides the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 86 publications
0
25
0
1
Order By: Relevance
“…There are increasing evidence that inflammatory mechanisms contribute to initiating or exacerbating psychiatric disorders 16 18 . Previous studies with major depressive disorder, schizophrenia, and generalized anxiety disorder showed that higher levels of IL-1β, IL-2, IL-6, and CCL2 were related to the severity of psychiatric symptoms 16 18 , 22 , 23 . However, there are only a few studies that suggested the relationship between psychiatric symptoms in epilepsy patients and inflammation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…There are increasing evidence that inflammatory mechanisms contribute to initiating or exacerbating psychiatric disorders 16 18 . Previous studies with major depressive disorder, schizophrenia, and generalized anxiety disorder showed that higher levels of IL-1β, IL-2, IL-6, and CCL2 were related to the severity of psychiatric symptoms 16 18 , 22 , 23 . However, there are only a few studies that suggested the relationship between psychiatric symptoms in epilepsy patients and inflammation.…”
Section: Discussionmentioning
confidence: 88%
“…CCL2 is a proinflammatory chemokine which causes neuroinflammation by promoting the chemotaxis of peripheral macrophages, T cells, and dendritic cells to the brain 22 , 23 . It is a possible mediator of the pathogenesis of depression since previous studies have demonstrated that serum CCL2 is elevated in major depressive disorder and reduced after antidepressant treatment 23 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…CCR2 was the receptor for Ccl2 in neurons, [ 31 ] and it is a G protein‐coupled receptor that binds G α i. [ 32 ] Recruitment of Ccl2 to CCR2 inhibited intracellular cAMP levels, which activates its downstream protein kinase A signaling pathway and plays a significant role in the development of depressive disorders. [ 33 ] Therefore, the Ccl2‐CCR2‐cAMP axis could be a potential machinery for the control of neuronal activities and the presence of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, chemokines have become a focus in the context of the development and treatment of brain diseases. Among them, chemokine CCL2 and its main receptor CCR2 have become candidate mediators of abnormal brain–immune-system dialogue in depression [ 19 ]. It has also been reported that an atypical chemokine receptor CCL2 binding, supports sustained inflammation and increased AD risk [ 20 ].…”
Section: Crossroads Of Neuroinflammation and Neurodegenerative Disordersmentioning
confidence: 99%